The political unconscious in the works of Robert E. Howard and Ernst Jünger - Burger, Patrick R.; Justus Liebig University Giessen (My University, 2014)
The book looks at these two figures of literature of the 1920s, 30s and 40s based on their similar strategies of the aestheticization of violence, their romance mythos narrative trajectories, and their resulting flirtations with fascism. The book s central argument is that the aftermath of World War I caused, on the one hand, a disillusionment with Western Civilization that made the figure of the Dionysian barbarian attractive on both sides of the Atlantic, and, concurrently, a new, cool psychological type based on the front soldiers of World War I, the kalte persona (cold persona). This psychological type characterized by emotional armour, the need for clearly defined psychological contours and the fear of laughability combined with the Dionysian barbarian discourse in a way that generated both Howard s super-heroic barbarian pulp-fiction romances and Jünger s apotheosis of the Front Soldier and Worker as heroic romance Gestalts striding victoriously across the age. These striking commonalities (underlined by a juxtaposition of amazingly similar battle scenes from their work) are, however, channeled into differing mythic narrative trajectories because of the international mythic meta-discourses codified in, for example, the Treaty of Versailles, and the resulting Kultur der Niederlage in Germany. As you may gather from this overview, this work combines the theories of Northrop Frye (narrative mythoi), Fredric Jameson (the political unconscious of texts), Helmut Lethen (Verhaltenslehre der Kälte), and Walter Schivelbusch (Kultur der Niederlage), among others, including Renate Lachmann (Phantastik und Neophantastik Schreibweisen) and J.R.R. Tolkien (theory of the Fantasy genre). The comparison of these two authors allows for insight into the process of how the tragedy of the fascist NS regime could have happened precisely because of their very similar aesthetic and mythic narrative starting points: Howard s ability to become a master of the Romance form contrasts with Jünger s ceaseless attempts to counter-act the meta-narrative cultural currents of Irony and Tragedy with his texts. Jünger s narrative deflections into Tragedy show how the cultural struggle to deal with the aftermath of World War I, particularly the assigning of romance villain status to Germany, led to amoral utterances in the barbarian discourse designed to re-assert a new vision of the romance hero.
Das politische Unbewußte in den Werken Robert E. Howards und Ernst Jüngers
Keywords: Robert E. Howard; Ernst Jünger; ddc:420